Parodia flmowa - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
Film parodies are now attracting more popular interest than at almost any time in their history except the first two decades of the 20th century (golden era of film parody). The contemporary renewal of parody is an attractive phenomenon of popular culture. To analyse and recontextualize this renewal of parodistic paradigm in film supporting by new media (spontaneous net art) Hendrykowski has compiled a wide-ranging panorama and collection of classic examples made by many famous but also unknown film-makers. Underlying the entire collection is the author’s personal belief that parody can be divers and rich as particular form of cultural rebellion and social catharsis – by turns comic effect and confusing dialogue in polemical confrontation with common opinion and public point of view established by parodied original.